Sosialisasi Gempur Rokok Ilegal di Desa Tonggara Kecamatan Kedungbanteng Kabupaten Tegal - Moh.Taufik; Sanusi Sanusi; Moh.Khamim; Fajar Ari Sudewo; Mukhidin Mukhidin (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Excise has a role to ensure that the circulation of certain excisable goods has met the distribution standards set by the government. Legal circulation of excisable goods is important so that people in consuming goods, such as tobacco products (cigarettes) have met the distribution standards, in addition to providing education to the community to participate in efforts to increase government revenue in terms of excise rates. Efforts to prevent illegal cigarettes will be effective if they involve various parties, both from law enforcement, universities and the community to help the state maximize state revenue. The goal to be achieved in this activity is to provide an understanding to students about the importance of understanding the importance of working together to prevent the circulation of illegal cigarettes in the community because in addition to having legal impacts on perpetrators and dealers, illegal cigarettes can also reduce state revenue.alization of illegal cigarettes